Pemuda Buddhayana: Membangun Karakter dan Kepemimpinan Buddha Melalui Aksi Sosial - Priono, Priono; Yudhawati, Ine; Dwi Kardana, Heru; Pujayanti, Vina (Kajian dan Reviu Jinarakkhita: Jurnal Gerakan Semangat Buddhayana (Jinarakkhita Review & Studies: Journal of Buddhayana Spirit Movement), 2024)
This research analyzes the impact of Buddhayana youth involvement in social activities on character and leadership development. The research method used is a qualitative approach with a case study in East Lampung Regency. The research results show that youth involvement in social activities contributes positively to character development such as empathy, responsibility, and caring, as well as leadership through effective communication, decision making, and time management. Social involvement also expands networks and builds positive relationships with the community. The implication is to support youth involvement in social activities for character development and responsible leadership. Future research could involve Buddhayana youth from other regions for a more comprehensive understanding